(untitled) (PANGEEA, 2025)
Globally, flooding is one of the natural catastrophes that annually causes the most victims and substantial economic damage. In European countries, flood-related deaths are relatively unusual, but damages to tangible assets and the cost to society are considerable. This paper presents a model for visualization of critical situations caused by flooding in rivers, based on critical factors derived from prior floods, hydrological models, and visualization models. The CRISSI model aims to provide common situational awareness by ensuring all authorities have the same information at the same time, without information overload.